Behavior and biocompatibility of rabbits bone marrow mesenchymal stem cells with bacterial cellulosic membrane - Alencar,Marcello Silva; Carvalho,Yulla Klinger; Carvalho,Camila Ernanda; Feitosa,Matheus Tajra; Carvalho,Fernando Aécio de Amorim; Viana,Bartolomeu Cruz; Miglino,Maria Angélica; Jozala,Ângela Faustino; Carvalho,Maria Acelina (PeerJ Preprints, 2017)
Introduction: Tissue engineering is being redesigned through promising studies that present great potential to create biomaterials capable of forming functional tissues. The cellular expansion and integration depends very much on the quality and adequacy of the surface of the scaffold being determinant for the success in the biological implants. The objective of this research was to characterize and evaluate in vitro the behavior of rabbits Bone Marrow Mesenchymal Stem Cells (BMMSC) when associated with Bacterial Cellulose Membrane (BCM) verifying the adhesion, expansion, cells integration into the biomaterial and the capacity macrophage activation as well as the evaluation of the bacterial cellulosic membrane cytotoxicity and toxicity. Materials and methods: Samples of rabbit bone marrow and mesenchymal stem cells were collected and mesenchymal stem cells were isolated from the medullary aspirates for fibroblast colony forming unit (CFU-F) assays, osteogenic and chondrogenic cellular differentiation induction, cellular integration study to the bacterial cellulosic membrane by Scanning Electron Microscopy (SEM) in the time interval of 1, 7 and 14 days as well as cytotoxicity (NO induction), BCM toxicity (MTT) and phagocytic activity. Results: The CFC-F assay showed cells with fibroblastoid morphology organized in colonies distributed across the culture area surface. In the growth curve two phases (lag and log) were observed in the course of 15 days. The cells multipotentiality was evident after osteogenic and chondrogenic lineages induction. Regarding the BMMSC bioelectrical integration to BCM, in the first 24 hours, the BMMSC were anchored in the BCM. On the seventh day of culture the cytoplasm was scattered and on fourteenth day the cells were fully integrated into the biomaterial. In the phagocytic activity assay there was a significant macrophages activation and for the nitric oxide concentrations and MTT analysis no cytotoxic biomaterial was observed. Conclusion: The bacterial cellulosic membrane allowed the bone marrow progenitor cells expansion and biointegration with stable cytotoxic profile thus presenting itself as biomaterial with potential for tissue engineering.
Keywords: Stem Cells; Tissue Engineering; Culture Techniques; Biocompatible Materials; Cellulose